Efficacy and safety of molecular targeted therapies in nasopharyngeal carcinoma: a network meta-analysis - Htet Htet; Jwala Rebacca James Anaghan; Heethal Jaiprakash; Ismail Abdul Sattar Burud; Thiruselvi Subramaniam; Igor Iezhitsa; Renu Agarwal (BMC Cancer)
Abstract Background Nasopharyngeal carcinoma (NPC) is one of the most common head and neck cancers worldwide. The majority of the new cases were from Asia and are the leading cause of cancer in China. The main treatment is surgery and radiotherapy with chemotherapy for advanced cases. With the advancement of targeted therapies, the objective of this study was to investigate the efficacy and safety of targeted therapies in NPC. Methods Databases were searched from inception to Aug 2023, comparing molecular targeted therapies (MTT) with conventional chemotherapy, chemotherapy or surgery. Study screening, data extraction, and data analysis were conducted independently by two investigators. The Cochrane Risk of Bias tool 1.0 was used for the quality of the studies. Results There was a total of ten eligible studies with 471 participants in the treatment arm and 469 participants in the control arm. Most studies had an unclear risk of bias assessment. Upon network meta-analysis, cetuximab was found to be the most effective regimen for complete response (CR), bevacizumab was found to be the most effective regimen for partial response (PR), nimotuzumab was found to be the most effective regimen for overall survival rate (OS) and progression-free survival (PFS). Pairwise meta-analysis showed that MTT had a significantly better response than conventional therapies in complete response. GRADE analysis reported low certainty of evidence for CR and very low certainty of evidence for other efficacy outcomes. There was a higher chance of bleeding with MTT and was statistically significant. Conclusion It was observed that targeted therapies were found to be a promising strategy for NPC especially recurrent and/or metastatic NPC, but the most appropriate therapy still needs to be evaluated. Trial registration This study was registered with the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY) with a registration number of INPLASY202380024.